A new Drosophila melanogaster fly that expresses GFP-tagged Orco - Jain, Kalpana; Stieber, Regina; Kaltofen, Sabine; Hansson, Bill S.; Wicher, Dieter (Frontiers in Ecology and Evolution, 2023)
Insects perceive countless odors with the help of odorant receptors (ORs) expressed by olfactory sensory neurons (OSNs). OR complexes are composed of odor-specific proteins OrX and olfactory co-receptor proteins Orco, both with extracellular C-terminus and intracellular N-terminus. Here, we generated a genetically modified Drosophila melanogaster fly line that expresses Orco proteins with N-terminally fused green fluorescent protein (GFP). We generated four genotypes (homozygous and heterozygous) for which we performed antennal cryosectioning and immunolabeling to determine which genotype would show high GFP labelling intensity in the dendritic areas of OSNs. We found that fluorescent intensity was the highest in homozygous flies. As Orco is known to guide OrX proteins to the OSN dendrites, we checked whether fusion of GFP to the Orco N-terminus may affect such trafficking and thereby OR function. Using single sensillum recording (SSR) we found no difference in the olfactory capability of homozygous flies compared to wild type flies. As future application, we want to use this transgenic fly line to resolve the structure of OR complexes using Cryo electron microscopy (cryo-EM).